BOOK REVIEW: Geacu Sorin, „Raul Călinescu – fondatorul biogeografiei româneşti”, Editura Curtea Veche, Bucureşti, 2019, 333 p. - MURARIU, Dumitru (Studia Universitatis Babeș-Bolyai Geographia, 2019)
Doctor Sorin Geacu, a devoted biogeographer, with PhD degree acquired in both Geography and Biology, senior researcher in the Institute of Geography of the Romanian Academy and a unique researcher and explorer of libraries and archives, provides us with impressive documentation on the life and scientific career of prof. dr. Raul Călinescu – the founder of the Romanian Biogeography.After the Foreward signed by the academician Dan Bălteanu – the Director of the Institute of Geography of the Romanian Academy –, the manuscript is organized into 29 chapters, which follow, chronologically, the main steps in the professional development of the distinguished biogeographer. The biogeographical data are supported through illustrated documents (e.g. Bachelor’s degree diploma in Geography – Natural Sciences; PhD and Docent diplomas in Biogeography). Graduate of the Faculty of Science of Cluj, under the mentorship of G. Vâlsan, R. Călinescu followed his urge to specialize in Biogeography. Moreover, working in the Zoology Laboratory of prof. A. Popovici-Bâz¬noşanu (Faculty of Sciences of Bucharest), Călinescu has acquired expertise in the determination of many vertebrate species. With E. Racoviţă, the promoter of the concept of species as morphological and geographical entities, as the President of his PhD Commission, Călinescu gained the ability to mainstream geographical concepts in his work. His 40-year teaching career was shortly related with the high school education, but it lasted much longer in the higher education, where he started his activity (from the time of his university studies) at the Botanical and Geography institutes of the Faculty of Sciences of Cluj University. In Bucharest, Călinescu began his activity at the Faculty of Sciences, first in the Laboratory of Descriptive Zoology and then, in the Laboratory of Physical Geography, evolving to the university assistant position in the Physical Geography Department, until 1956, when he became a full professor in Biogeography at the University of Bucharest. These main steps in his teaching career are illustrated through copies of 12 documents, as well as through 27 photos reflecting moments from the field works with his students.